Parliamentary Life and Democracy in 21st Century Britain - KHEDDAR, Mustapha (My University, 2017)
Parliament is a place where people can speak or discuss matters and interests of the population, and where all the points of view are held, those who argue, try to persuade or support and those who oppose. It is a place where all the political parties aim at a variety of goals. Nowadays, most people think that parliament is the best form of government which achieves a sort of democratic system, and it is considered as the sovereign legislative authority in the state. Parliament is considered as the essential part of the political life in Britain and in citizens’ life, by which democracy can be reached, because the right policies result more from discussion shared by many persons than from decisions taken by a minority. Accordingly, elected individuals ought to recognize local, national and international interests. In Britain, parliament is the supreme legislative authority and has legal independence in virtually all matters, and for some politicians is not, and it is a difficult task to restrain the power of the executive. Parliament has two essential chambers; the House of Commons and The House of Lords. Each chamber has its own works and functions.
Keywords: Great Britain; Modern institutions; Parliament; Policies